RNA diversification by a self-reproducing ribozyme revealed by deep sequencing and kinetic modelling. Issue 61 (8th July 2021) - Jeancolas, Cyrille; Matsubara, Yoshiya J.; Vybornyi, Mykhailo; Lambert, Camille N.; Blokhuis, Alex; Alline, Thomas; Griffiths, Andrew D.; Ameta, Sandeep; Krishna, Sandeep; Nghe, Philippe
Abstract : The integration of self-reproduction and diversification mechanisms in RNA reaction networks paves the way for experimental tests of prebiotic evolution. Abstract : We demonstrate that a recombinase ribozyme achieves multiple functions in the same reaction network: self-reproduction, iterative elongation and circularization of other RNAs, leading to synthesis of diverse products predicted by a kinetic model. This shows that key mechanisms can be integrated and controlled toward Darwinian evolution in RNA reaction networks.